BipC, a Predicted Burkholderia pseudomallei Type 3 Secretion System Translocator Protein with Actin Binding Activity - Vander Broek, Charles W.; Zainal Abidin, Nurhamimah; Stevens, Joanne M. (Frontiers in Cellular and Infection Microbiology, 2017)
Burkholderia pseudomallei is an intracellular bacterial pathogen and the causative agent of melioidosis, a severe disease of humans and animals. Like other clinically important Gram-negative bacteria, fundamental to B. pseudomallei pathogenesis is the Bsa Type III Secretion System. The Bsa system injects bacterial effector proteins into the cytoplasm of target host cells subverting cellular pathways for the benefit of the bacteria. It is required for invasion of non-phagocytic host cells, escape from the endocytic compartment into the host cell cytoplasm, and for virulence in murine models of melioidosis. We have recently described the repertoire of effector proteins secreted by the B. pseudomallei Bsa system, however the functions of many of these effector proteins remain an enigma. One such protein is BipC, a homolog of the translocator/effector proteins SipC and IpaC from Salmonella spp. and Shigella flexneri respectively. SipC and IpaC each have separate and distinct roles acting both as translocators, involved in creating a pore in the eukaryotic cell membrane through which effector proteins can transit, and as effectors by interacting with and polymerizing host cell actin. In this study, pull-down assays demonstrate an interaction between BipC and actin. Furthermore, we show that BipC directly interacts with actin, preferentially with actin polymers (F-actin) and has the ability to polymerize actin in a similar manner as that described for SipC. Yet unlike SipC, BipC does not stabilize F-actin filaments, indicating a functionally distinct interaction with actin. Expression of Myc-tagged BipC in HeLa cells induces the formation of pseudopodia similar to that seen for IpaC. This study explores the effector function of BipC and reveals that actin interaction is conserved within the BipC/SipC/IpaC family of translocator/effector proteins.